Knowledge atlas and emerging trends on ncRNAs of osteosarcoma: A bibliometric analysis - Wang, Bo; Yang, Chunhua; Zhou, Chuqiao; Xiao, Shipeng; Li, Hui (Frontiers in Endocrinology, 2022)
Background: Osteosarcoma is a common bone sarcoma that occurs in childhood and adolescence. Although research on ncRNAs of osteosarcoma has been developed rapidly in recent years, a specific bibliometric analysis on this topic has not yet been performed. The bibliometric analysis aims to summarize knowledge atlas, research hotspots and emerging trends and to provide researchers with new perspectives in further studies. Methods: All publications regarding ncRNAs of osteosarcoma published from 2000 to 2021 were retrieved from the Web of Science Core Collection. Quantitative indicators including number of publications and citations, H-index, and journal citation reports were analyzed by using Excel 2019 and R software. VOSviewer and CiteSpace were used to analyze the cooperation among countries/institutions/journals/authors, and the co-occurrence of keywords, keywords bursts, and references. Results: A total of 3206 publications were extracted. A significant growth trend in the annual number of publications over the past 22 years is revealed (R2 = 0.999). The most prolific country and institution were China (2260) and the Shanghai Jiao Tong University (134), respectively. Professors Wang W and Liu W contributed most to this field. The keywords were stratified into six clusters: cluster 1 (apoptosis and growth); Cluster 2 (cancer and progression); Cluster 3 (microRNAs and down-regulation); Cluster 4 (genes and differentiation); Cluster 5 (expression and biological functions) and Cluster 6 (metastasis). The long non-coding RNAs and circular RNAs have been considered as an important research hotspot in the near future. Conclusion: This study offers a scientific perspective on ncRNAs of osteosarcoma and provides researchers with valuable information to understand the knowledge structure and to identify emerging trends in this field.